SKRINING FITOKIMIA DAN PARAMETER NON SPESIFIK EKSTRAK ETANOL AKAR BAJAKAH (spatholobus littoralis Hassk.) - Dwi Nursyafitri; Ade Ferdinan; Fitri Sri Rizki (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
Phytochemical screening research and non-specific parameters of the ethanol extract of pirated roots (have been carried out Spatholobus littoralis Hassk.). The results of the phytochemical screening test of pirated roots (Spatholobus littoralis Hassk.) contained alkaloids, flavonoids, tannins, phenols, and saponins. The non-specific parameter test results that meet the requirements include drying shrinkage 2.45%, the water content test is 2.398%, the specific gravity test is 0.8390%, the total ash content test was 0,964%, and did not meet the requirements of the acid insoluble ash content test of 1.557%.